A review of goat reproduction in East and Horn of Africa - Rouatbi, Mariem; Haile, Aynalem; Getachew, Tesfaye; Dione, Michel; Zannou, Olivier; Tebourbi, Ons; Idoudi, Zied; Rischkowsky, Barbara; Rekik, Mourad (ICARDA, 2022)
While goats are an important pillar of livestock and agriculture sectors in East and Horn of Africa, little research is being published and access to unpublished data is very difficult. This working paper attempts to review the male and female reproductive characteristics of goats in 11 countries of East and Horn of Africa (Burundi, Djibouti, Eritrea, Ethiopia, Kenya, Malawi, Rwanda, Somalia, Sudan, Tanzania and Uganda), and to summarize studies that have looked at the improvement of reproductive performance of goats, and applications of reproductive biotechnologies, such as artificial insemination and embryo transfer. A section of this paper is dedicated to reviewing the main diseases affecting the reproduction of goats, and analyzing prevalence and main risk factors. This working paper is a first step to fill a gap in knowledge related to reproduction in goats. The volume and quality of information between countries varied considerably, so there are some disproportions in reporting findings and results for certain traits.